Micrometrology in pursuit of quantum radiation standards. (December 2021) - Fitzgerald, Ryan; Ahmed, Zeeshan; Bergeron, Denis; Klimov, Nikolai; Schmidt, Daniel; Tosh, Ronald
Abstract: With the recent redefinition of the SI base units in terms of constants of nature, the race is on to maximize achievable precision by developing primary standards based on quantum metrology, thereby to realize the Quantum SI. For the becquerel (Bq) and gray (Gy), the derived SI units for activity and absorbed dose, respectively, this is especially challenging because production and detection of ionizing radiation is difficult to manage at the atomic scale, and quantum coherences are easily lost in the cascade of inelastic processes that accompany the slowing of energetic particles in matter. This would not preclude a secondary role for quantum metrology in the pursuit of single-event detection and resolution of radiation effects at microscopic scales, where we are beginning to apply new transition-edge sensors, silicon photonics, and link to quantum electrical standards. Here we summarize recent results for microcalorimetry in activity and dosimetry measurements and discuss their potential as next-generation standards.